(untitled) (Papeles, 2011)
Educational research specifically related to teacher training in the analysis of the life stories of a strategy that allows us to understand individual ideas related to the training process to configure collective conceptions associated with political factors social and cultural. This papper outlines the conceptual and research master’s thesis entitled “Conceptions and reflections on teacher education from stories educational life “centered on the interpretation of the concepts and ideas related to the training of teachers, which were found in the professional life stories of the participants in this study.